2018
DOI: 10.1097/md.0000000000013783
|View full text |Cite
|
Sign up to set email alerts
|

Association of allergic rhinitis with obstructive sleep apnea

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 65 publications
(31 reference statements)
3
40
1
1
Order By: Relevance
“…To the best of our knowledge, this is the first systematic review and meta-analysis evaluating the association between AR and sleep based on observational investigations. A 2018 systematic review focused on the association between AR and OSA and applied a meta-analysis of population-based studies; however, this article concentrated mainly on the prevalence of AR in subjects with or without OSA/SDB [63]. Another related review examined AR and sleep impairment, but focused mainly on the mechanism of their association and the consequences of disordered sleep [64][65][66][67][68][69][70][71].…”
Section: Assessment Of Cumulative Evidencementioning
confidence: 99%
“…To the best of our knowledge, this is the first systematic review and meta-analysis evaluating the association between AR and sleep based on observational investigations. A 2018 systematic review focused on the association between AR and OSA and applied a meta-analysis of population-based studies; however, this article concentrated mainly on the prevalence of AR in subjects with or without OSA/SDB [63]. Another related review examined AR and sleep impairment, but focused mainly on the mechanism of their association and the consequences of disordered sleep [64][65][66][67][68][69][70][71].…”
Section: Assessment Of Cumulative Evidencementioning
confidence: 99%
“…Cao et al in their meta-analysis, showed that in adults the incidence of AR in OSA patients was 35.2 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the AASM Manual for the Scoring of Sleep and Associated Events, OSA severity was classified on the basis of the apnea + hypopnea index (AHI) [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly to our study, Juniper et al [21] reported that AR symptoms were related with discomfort to patients and negative impact in quality of life in general. In addition, Maspero et al [26] and Schatz [27] Indeed regarding the obstructive sleep apnea, Cao et al [46] reported that the prevalence of AR in obstructive sleep apnea (OSA) was considerably high and children with sleep-disordered breathing suffered from a higher incidence of AR than non-sleep-disordered breathing. However OSA adults accompanied with AR did not have any influences on sleep parameters [46].…”
Section: Discussionmentioning
confidence: 99%